Liver Abscess Not An Uncommon Disease - Hayat, Zafar; Mahmood, Sultan; Ali, Muhammad; Nishtar, Tariq; Sartaj, Farsheed; Naeem, Fayaz; Khan, Pir Muhammad; Islam, Noor ul; Jan, Mian Asad Ullah (Journal of Postgraduate Medical Institute, 2011)
A prospective study of 50 cases of liver abscess was conducted in Hayat Shaheed Teaching Hospital, Peshawar over years 1991-1995. There were 35 male and 15 female patients: the age range between 16-70 years. Common presentation was fever (95%) common signs were hepatomegaly and point tenderness in right lower intercostal spaces posterolateral (80%). Definite diagnostic test was ultrasound and in some cases CT scan of the abdomen. Raised alkaline phosphatase (95%) and PMN Leucocytosis (70%) were ancillary diagnostic tests. Treatment in case of amoebic liver abscess was tailored according the size of the abscess and the impending complications. Treatment was stratified as: Medical alone (Metronidazloe), Medical and percutaneous needle aspiration under ultrasound guidance and Medical plus surgical drainage. Morbidity and mortality due to needle aspiration under ultrasound guide were insignificant. Relapse rate in our study was insignificant for both amoebic and pyogenic liver abscesses. Treatment in case of single pyogenic liver abscess was surgical drainage or needle aspiration plus intravenous antibiotics preferably according to the available culture sensitivity reports. Multiple pyogenic abscesses complication a primary illness were treated by aspiration / surgical drainage and treatment of the parent disease i-e enteric fever and SBE.